MENOPAUSA E SÍNDROME METABÓLICA: EFEITOS DO TREINAMENTO FÍSICO AERÓBIO E RESISTIDO NO ESTRESSE OXIDATIVO MUSCULAR EM MODELO EXPERIMENTAL - VIEIRA, Adeilson Serra Mendes (2021)
Introduction: Menopause associated with cardiovascular risk factors, cause damage to women's health and can exacerbate the oxidative stress profile in body tissues. On the other hand, it is known that physical exercise is an effective method in the treatment and / or prevention in different situations with regard to health damage. The understanding of how physical training affects the behavior of oxidative stress in skeletal muscle, can contribute with relevant information for the treatment of menopausal women with metabolic syndrome. Objective: To evaluate the effects of aerobic and resistance training in an experimental model of menopause and metabolic syndrome focusing on the role of oxidative muscle stress. Métodos: This study is an in vivo experimental type. For sample, 8 female Wistar rats and 40 female SHRs were used, equally divided into 6 groups: normotensive (C), hypertensive (H), oophorectomized hypertensive (HO), oophorectomized hypertensive women treated with fructose (HOF), submitted to aerobic physical training (HOFTa) or resistance physical training (HOFTr). Aerobic physical training (treadmill; 1h / day; 5x / week) and resistance physical training (ladder adapted for rats; 1h / day; 5x / week) were performed for 8 weeks. After 19 weeks of protocol, metabolic parameters, functional capacity, damage to cell membrane and muscle tissue proteins, activity of the superoxide dismutase enzyme and the concentration of the catalase enzyme were evaluated. The two way analysis of variance test (ANOVA) followed by Tukey's post hoc were used for data analysis in the GraphPad Prism 5 program, adopting p <0.05 as significant. Resultados: In the present study, both physical training were able to improve functional capacity in tests of maximum effort (HOF: 22 ± 3.17 vs. HOFTa: 30 ± 0.87 min) and maximum load (HOF: 412 ± 52.80 vs. HOFTr: 550 ± 39.60 g). Body weight decreased with resistance physical training (HOF: 260 ± 7.92 vs. HOFTr: 245 ± 7.92 g). In turn, aerobic physical training reduced blood glucose (HOF: 94 ± 5.54 vs. HOFTa: 79 ± 4.75 mg / dL). Triglycerides showed an increase with the association of risk factors. However, it was mitigated with aerobic physical training. Both physical training attenuated the reduction in insulin sensitivity generated by the association of risk factors. Resistance physical training reduced the catalase enzyme concentration in relation to the hypertensive group (H: 0.21 ± 0.05 vs. HOFTr: 0.12 ± 0.07 nmol / mg protein). Superoxide dismutase activity was attenuated by aerobic physical training. Conclusion: The induction of the menopause model has already been disclosed in a previous study, confirming that there was a deprivation of ovarian hormones. The metabolic parameters in the present study proved that the model is also syndromic. However, aerobic physical training was effective in improving functional capacity, reducing glycemia, attenuating triglyceridemia and superoxide dismutase enzyme activity. On the other hand, resistance physical training was effective in also improving functional capacity, body weight and attenuating the catalase enzyme concentration.